2021
DOI: 10.1016/j.celrep.2021.108987
|View full text |Cite
|
Sign up to set email alerts
|

Intensive longitudinal characterization of multidimensional biobehavioral dynamics in laboratory rats

Abstract: Highlights d Bistable evolution of rat behavior during development and depends on sex and strain d Big data analysis reveals circatidal-like rhythms in locomotor activity d Thigmotaxic behavior in home-cage may be driven by random walk and not stress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Given the broad range of temporal scales covered by the dynamic pattern of rhythms, it is important to separate low-frequency high-amplitude from high-frequency low amplitude rhythms. In addition to the circadian rhythm, the first regimen comprises the ~ 12 h circatidal-like rhythm, not only documented in coastal organisms 64 but also in the locomotor activity of quails 23 and rats, as recently shown by Hasanpour and collaborators 65 , whom by comparing the circatidal-like rhythm with the artificial light/dark cycles (12L:12D) using phase-synchronicity analysis observed that the detected circatidal rhythm is unlikely to have been caused by the experimental setup. In addition, herein, we also show evidence of an 8 h rhythm in activity patterns.…”
Section: Discussionmentioning
confidence: 89%
“…Given the broad range of temporal scales covered by the dynamic pattern of rhythms, it is important to separate low-frequency high-amplitude from high-frequency low amplitude rhythms. In addition to the circadian rhythm, the first regimen comprises the ~ 12 h circatidal-like rhythm, not only documented in coastal organisms 64 but also in the locomotor activity of quails 23 and rats, as recently shown by Hasanpour and collaborators 65 , whom by comparing the circatidal-like rhythm with the artificial light/dark cycles (12L:12D) using phase-synchronicity analysis observed that the detected circatidal rhythm is unlikely to have been caused by the experimental setup. In addition, herein, we also show evidence of an 8 h rhythm in activity patterns.…”
Section: Discussionmentioning
confidence: 89%
“…It has been well‐known that music played with harmonic notes is the most pleasant to the ears. Like music, biological ultradian rhythms also tend to cycle at the harmonic frequencies of the 24‐h, namely, at the ultradian periods of 12‐h, 8‐h, 6‐h, etc., ranging from the transcriptome, proteome, metabolome to behavior levels 19–32. Interestingly, the harmonic periods usually vary concordantly with the exact period of the circadian rhythm under various physiological conditions.…”
Section: Ultradian Rhythms Predominantly Cycle At the Harmonic Freque...mentioning
confidence: 99%
“…[19,35,46] Superimposed 12-h rhythms of locomotive activity were also reported in both mice and rats under standard laboratory 12-h light/12-h dark conditions. [25,47] Because this is a liver-centric review, we will not elaborate on the topic of 12-h rhythms in extrahepatic tissues, the topic of which was extensively discussed elsewhere. [35,46] Evidence supporting the existence of an XBP1s-dependent 12-h oscillator Several theories have been put forward over the past decade to account for the regulation of hepatic 12-h rhythms.…”
Section: -H Rhythms Of Gene Expression Are Prevalentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to liver, wide prevalence of ~12-hour rhythms of gene expression were further identified in murine white adipose tissue, brown adipose tissue, adrenal gland, aorta, muscle and cornea using multiple mathematical/statistical methods (7,(10)(11)(12)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Using spectrum analytic methods including Fourier, wavelet, autocorrelation analysis and eigenvalue/pencil, ~12-hour rhythms of locomotor activity, energy homeostasis and/or feeding rhythms were also uncovered from rodents (8,11,26).…”
Section: Introductionmentioning
confidence: 99%